Multi-version to ensure the integrity of information: experiments and results - Харченко, В. С.; Халин, М. Б. (Problems of Informatization and Control, 2004)
There are offered some methods and structural solutions on implementation the multiversion digital signature with usage diversion hashing functions. There are listed results of machine experiment on testing of such solutions are resulted